AL-MUHASSINĀT AL-BADI'IYYAH PADA AYAT-AYAT HUKUM TENTANG BERJUANG DI JALAN ALLAH - Ardiansyah Ardiansyah (Fakultas Syariah (Syari'ah Faculty ), 2016)
Language characteristic of law is independent, unemotional, and plain in order to avoid ambiguity. Al-Quran with the perfection and miracle of its language make it different from other law sources. This writing addresses the language style of Quranic verses discussing law: the duty to do jihad for the sake of Allah. The verses will be identified using Badi’ study byelaborating not only their beautiful meaning (al-muhassināt alma’nawiyah) but their beautiful lafadz (al-muhassināt al-lafdziyah) as well. There are nine muhassināt found in this study. These beauties include meaning (al-muhassināt alma’nawiyah) and lafadz (al-muhassinat al-lafdziyah). Al-Muhassināt al-Ma’nawiyah found in these verses consists of four kinds: Tibaq, Tauriyah, Jam and Taqsim, while al- Muhassināt al-Lafdziyah includes two softs of beauties, they are Jinas and Radd al-A’jz ala al-Sadr. These findings prove that the verses do not address jihad emotionally but discuss it beautifully and calmly. Keywords: Ilmu badī’, al-muhassināt al-ma’nawiyah, al-muhassināt al-lafdziyah, verses law.